Case Report: A Chinese Family of Woodhouse-Sakati Syndrome With Diabetes Mellitus, With a Novel Biallelic Deletion Mutation of the DCAF17 Gene - Zhou, Min; Shi, Ningjie; Zheng, Juan; Chen, Yang; Wang, Siqi; Xiao, Kangli; Cui, Zhenhai; Qiu, Kangli; Zhu, Feng; Li, Huiqing (Frontiers in Endocrinology, 2021)
Woodhouse–Sakati syndrome (WSS) (OMIM#241080) is a rare multi-system autosomal recessive disease with homozygous mutation of the DCAF17 gene. The main features of WSS include diabetes, hypogonadism, alopecia, deafness, intellectual disability and progressive extrapyramidal syndrome. We identified a WSS family with a novel DCAF17 gene mutation type for the first time in China. Two unconsanguineous siblings from Chinese Han family exhibiting signs and symptoms of Woodhouse-Sakati syndrome presented for evaluation. Whole exome sequencing revealed a homozygous deletion c.1287_1288delAG in the DCAF17 gene, resulting in a frameshift within premature stop codon formation. We found that two patients exhibited low insulin and C-peptide release after glucose stimulation by insulin and C-peptide release tests. These findings indicated that DCAF17 gene mutation might lead to the pancreatic islet function impairment and further contribute to the development of diabetes.